2008
DOI: 10.14710/reaktor.12.1.53-57
|View full text |Cite
|
Sign up to set email alerts
|

Pembuatan Kitosan Dari Limbah Cangkang Udang Serta Aplikasinya Dalam Mereduksi Kolesterol Lemak Kambing

Abstract: Kitosan adalah hasil proses deasetilasi dari senyawa kitin yang banyak terdapat dalam kulit luar hewan golongan Crustaceae seperti udang dan kepiting. Bila dikonsumsi di dalam tubuh manusia Kitosan bisa berfungsi menyerap lemak. Kemampuan Kitosan untuk menyerap lemak tergantung pada derajat deasetilasinya. Percobaan dibagi dalam dua tahap. Tahap pertama adalah pembuatan Kitosan dari kulit udang, dengan variasi konsentrasi NaOH masing-masing 20, 30, 40 dan 50% (% berat). Kitosan yang dihasilkan dari proses ini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
1
11
0
7
Order By: Relevance
“…In addition, the positive chitosan is able to react with the surface of negative anionic polymer, so it can facilitate the migration of inflammatory cells. 22,23 Based on several studies on chitosan as described above, it can be said that chitosan still needs to be developed since it has some potential functional characters for broad use in dentistry. Finally, it can be concluded that the deacetylation degree of chitosan derived from white shrimp shells could reach 85.165%.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the positive chitosan is able to react with the surface of negative anionic polymer, so it can facilitate the migration of inflammatory cells. 22,23 Based on several studies on chitosan as described above, it can be said that chitosan still needs to be developed since it has some potential functional characters for broad use in dentistry. Finally, it can be concluded that the deacetylation degree of chitosan derived from white shrimp shells could reach 85.165%.…”
Section: Methodsmentioning
confidence: 99%
“…Chitin was prepared from shrimp shell [9], and colloidal chitin was prepared by the addition of HCl [10]. The chitin broth for chitinase production was made of KH2PO4 (0.03%), K2HPO4 (0.07%), MgSO4.5H2O (0.05%), ZnSO4 (0.0001%), MnCl2 (0.0001%), starch (1.5%), yeast extract (0.15%) and colloidal chitin (1.5%).…”
Section: Medium and Inoculum Preparationmentioning
confidence: 99%
“…Pembuatan kitin mengacu pada Hargono & Sumantri (2008), sedangkan koloidal kitin mengacu pada Arnold & Solomon (1986).…”
Section: Metode Penelitianunclassified